Hyperemesis Gravidarum and Obstetric Outcome - Giri, A; Tuladhar, AS; Tuladhar, H (Nepal Journal of Obstetrics and Gynaecology, 2012)
Aims: This study was conducted to evaluate maternal characteristics and obstetric outcomes among women with hyperemesis gravidarum during pregnancy. Methods: A prospective hospital based study was conducted at Nepal medical college and teaching hospital over the period of two years where all the women admitted with history of hyperemesis gravidarum were evaluated. Hyperemesis gravidarum was defined as intractable nausea/vomiting in pregnancy that leads to dehydration, nutritional deficiency, electrolyte and metabolic disturbances and considerable ketonuria that may require hospitalization. The age of women, parity, gestational age, method of treatment and duration of hospital stay were analysed.The fetal outcome evaluated were incidence of preterm birth, apgar score <7 at 5 mins of birth, low birth weight, perinatal deaths and congenital anomalies in baby. Results: There were 52 women admitted with hyperemesis gravidarum among all obstetric admission (N= 2080). The incidence of hyperemesis gravidarum was 2.5% of all pregnancy. The condition was seen more commonly in nulliparous (61.5%) than in multiparous women. It was less common in women of parity 3 or more. The problem was identified maximum (50%) in gestational age of 5-7 weeks though one case was seen in gestational age of 20 weeks also. The mainstay of treatment was supportive. The range of hospital stay was 1-10 days with mean hospital stay 2.26 days. The preterm delivery rate was 4.8% and none of the babies were low birth weight. All the babies had apgar score >7 at 5 mins of birth. There were no congenital anomalies and no perinatal deaths were noted. Conclusions: Women with hyperemesis gravidarum did not have adverse obstetric outcome in this study. NJOG 2011 Nov-Dec; 6 (2): 24-26 DOI: http://dx.doi.org/10.3126/njog.v6i2.6752